El The Compressed Ground Block or BTC A Construction Alternative for Contemporary Architecture (2019)
The degradation of the planet has led both research and experimentation organizations, as well as private and private companies to propose new and better construction alternatives that minimize the negative environmental impact for fauna, flora and natural resources in general. Many of these alternatives take up vernacular building systems and materials that are friendly to nature, such as land for construction. This is why the compressed earth block or BTC is one of the most representative construction techniques in land, due to its possibility of industrialization and large-scale production in a fast and economic way; what makes it a viable, durable and sustainable alternative for all types of work as it behaves like a traditional prefabricated one with the difference that it does not produce CO2 , that is why this article aims to show the benefits of this material and contextualize it in the present.